2012
DOI: 10.4103/0028-3886.96394
|View full text |Cite
|
Sign up to set email alerts
|

The etiological diagnosis and outcome in patients of acute febrile encephalopathy: A prospective observational study at tertiary care center

Abstract: In this study, pyogenic meningitis was the leading cause of AFE, followed by AVE and cerebral malaria. The outcome in cases with AVE can be fatal or more disabling than other etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 9 publications
3
36
1
Order By: Relevance
“…In the study by Modi et al of out 120 patients, pyogenic meningitis was found in 44 (36.7%) was the commonest etiology followed by acute viral encephalitis (AVE) 34 (28.33%). [1,10] In present study as well as in study done by Bhalla et al1 and Modi et al4 the maximum burden of disease was of pyogenic meningitis and viral meningoencephalitis. But there was difference in percentage of various etiologies.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In the study by Modi et al of out 120 patients, pyogenic meningitis was found in 44 (36.7%) was the commonest etiology followed by acute viral encephalitis (AVE) 34 (28.33%). [1,10] In present study as well as in study done by Bhalla et al1 and Modi et al4 the maximum burden of disease was of pyogenic meningitis and viral meningoencephalitis. But there was difference in percentage of various etiologies.…”
Section: Discussionsupporting
confidence: 74%
“…[1] In present study 30.43% of the patients had seizures which was in concordance with our study. Fever, headache and altered sensorium were also the most common presenting complaints of patients in other studies by Kashinkunti et al and Modi et al [10,11] In our study a total of 48 (41.73%) patients had acute pyogenic/bacterial meningitis. Twenty four patients (20.86%) had viral meningoencephalitis.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…To the best of our knowledge, data thoroughly assessing the predictors of unfavorable outcome in HME patients do not exist in the literature. One more potential limitation of the studies published was that they included cases without virological confirmation (11)(12)(13), thus blurring the inferences made. Hence, in this multinational study, we included only HME patients with a definite virological diagnosis.…”
mentioning
confidence: 99%